Levels and Determinants of age at first marriage in Namibia - Amutenya, Loide T A (Division of Actuarial Science, 2024)
Age at first marriage is the age at which one gets married for the first time. This study examines the trends and socio-economic factors of age at first marriage in Namibia this topic has been under researched and as a result a gap in the knowledge exists. This research aims to determine age at marriage across different social demographic characteristics well to determine factors associated with age at first marriage. Data from NDHS for the years 1992, 2000, 2006 and 2013, are used in this study and The Hajnals SMAM was used to determine the trends in ages. Results showed that in 1992, Namibian women remained single for 26 years, 28 years in 2000, 29 years in 2006/07 and 30 years in 2013. The study also used the Kaplan Meier and Cox proportional hazard regressions to explain the factors associated with age at first marriage for each survey year. Results revealed selection effects on age at marriage among women in the 15-24 age group. An increase in age, commencement in sexual activity, premarital birth, first birth, and better educational opportunities decrease the risk associated with early marriage. The study also found that the Northeast region which comprised of Kavango East, Kavango West and Zambezi/Caprivi region had the highest risk of early marriage compared to other regions. Overall, there was significant decrease in age at first marriage across all age groups. The results also showed that this delay was linear with an increase in premarital births, however there is still a general decline in fertility rates